The Wheel of time : the Shamans of ancient Mexico, their thoughts about life, death and the universe - Castaneda, Carlos, 1931-1998 (Washington Square Press, 2001)
Contains a selection of quotations, collected by the author from his works on his training as a shaman initiate, including "The Teachings of Don Juan," "Journey to Ixtlan," " A Separate Reality," and "Tales of Power."